2015
DOI: 10.1016/j.bbadis.2015.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Signaling pathways underlying skeletal muscle wasting in experimental pulmonary arterial hypertension

Abstract: Henriques-Coelho, Signaling pathways underlying skeletal muscle wasting in experimental pulmonary arterial hypertension, BBA -Molecular Basis of Disease (2015),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 49 publications
3
23
1
1
Order By: Relevance
“…The role of TGFβ proteins in muscle wasting in PAH has not been widely analysed, being limited to one study showing increased circulating myostatin in MCT-treated rats 29. We have identified, as is the case in ICUAW,12 COPD14 and cancer,30 that PAH-associated muscle loss may also be a GDF-15 driven phenomenon.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The role of TGFβ proteins in muscle wasting in PAH has not been widely analysed, being limited to one study showing increased circulating myostatin in MCT-treated rats 29. We have identified, as is the case in ICUAW,12 COPD14 and cancer,30 that PAH-associated muscle loss may also be a GDF-15 driven phenomenon.…”
Section: Discussionmentioning
confidence: 91%
“…5(Z)-7-oxozeanol has been used to antagonise TAK1 in a number of animal models of disease including autoimmune diabetes35 and cerebral ischaemia 20. TAK1 inhibitors may be more successful than other more specific drugs aimed at antagonising muscle loss, as they have the potential to inhibit these synergistic muscle wasting pathways 29…”
Section: Discussionmentioning
confidence: 99%
“…58 The skeletal muscle is particularly sensitive to insulin resistance and metabolic syndrome, and indeed, the skeletal muscle of PAH patients exhibits signs of such abnormalities as well as mitochondrial dysfunction ( Figure 2D). 59 Proteomic analysis of PAH skeletal muscles revealed decreased expression of PDH and increased expression of glycolytic enzymes (eg, lactate dehydrogenase), as well as abnormal mitochondrial morphology suggestive of a glycolytic metabolism shift. 59,60 This finding is significant because it suggests that the impaired mitochondrial and metabolic functions observed in the cardiopulmonary system are also present in extrapulmonary tissues.…”
Section: Altered Metabolism In Skeletal Musclementioning
confidence: 99%
“…Another study demonstrated that mitochondria isolated from the gastrocnemius muscle of MCT rats are characterized by ATP synthase activity, decreased expression of transcription factor A, mitochondrial (TFAM, a DNA-binding protein that activates transcription of mitochondrial DNA), and accumulation of oxidatively modified proteins, suggesting that mitochondria from these animals are unable to efficiently clear damaged or misfolded proteins, thus contributing to muscle atrophy in PAH. 59 Finally, while most studies focused on metabolic disorders in PAH, a recent study demonstrated that in a novel model of PH from heart failure with preserved ejection fraction (PH-HFpEF), chronic nitrite or metformin treatment reduce hyperglycemia and attenuate PH endpoints via a sirtuin 3 (SIRT3)-AMPK-GLUT4 dependent signaling pathway in the skeletal muscle, suggesting that glucose uptake and mitochondrial function in the skeletal muscle are linked to systemic glucose levels and pulmonary vascular function. 61…”
Section: Altered Metabolism In Skeletal Musclementioning
confidence: 99%
“…Similarly, a switch to a less fatigue-resistant phenotype (lower proportions of slowtwitch fibres) and increased anaerobic metabolism have been demonstrated in the lower limb muscles of patients with PAH [82][83][84] . Furthermore, an anabolic/catabolic imbalance (increased proteolytic markers and reduced mitochondrial ATP production) has been recently demonstrated in the gastrocnemius and blood in an experimental model of PAH together with significant body and muscle weight loss 85 . In view of these findings, pulmonary rehabilitation and exercise training have recently gained a lot of attention in the scientific community to alleviate skeletal muscle dysfunction and exercise intolerance in patients with PAH 80,86 .…”
Section: Pulmonary Arterial Hypertensionmentioning
confidence: 99%